Post-fire, seasonal and annual dynamics of the ectomycorrhizal community in a Quercus ilex L. forest over a 3-year period. (Mycorrhiza, 2005)
Two study plots, burned and control, were established in autumn 1998 in a Quercus ilex forest located in northern Spain, part of which had been affected by a low intensity fire in 1994. Soil samples for ectomycorrhizae (ECM) were taken over a 3-year period in each study plot in spring, summer, autumn and winter. ECM morphotypes were identified and the relative abundance of each morphotype in each soil sample calculated, along with species richness, Shannon diversity index and percentage of mycorrhization in each soil sample. The relative abundance of certain ECM morphotypes differed between burned and control plots, and the percentage of mycorrhizal tips was significantly lower in the burned than in the control plot. Nevertheless, there were no significant differences in the diversity, species richness or species composition of the ECM community in the burned and control plots. The dominant ECM morphotypes in both stands were Cenococcum geophilum and several thelephoroid fungi. Sphaerosporella brunnea and Pisolithus tinctorius thrived especially in the burned plot, whereas three ectomycorrhizal morphotypes assigned to the genus Hebeloma were especially abundant in the control plot. There was no significant variation in the relative abundance of the ECM morphotypes between seasons, but ECM community species richness was highest in autumn and lowest in summer. The percentage of mycorrhizal tips reached a maximum in winter, with its minimum in autumn. Collection of samples over the 3-year period also enabled us to detect a significant increase in percentage of ECM colonisation in the burned stand over time.

Post-fire, seasonal and annual dynamics of the ectomycorrhizal community in a Quercus ilex L. forest over a 3-year period. - De Roman, Miriam; de Miguel, Ana María (Mycorrhiza, 2005)
Two study plots, burned and control, were established in autumn 1998 in a Quercus ilex forest located in northern Spain, part of which had been affected by a low intensity fire in 1994. Soil samples for ectomycorrhizae (ECM) were taken over a 3-year period in each study plot in spring, summer, autumn and winter. ECM morphotypes were identified and the relative abundance of each morphotype in each soil sample calculated, along with species richness, Shannon diversity index and percentage of mycorrhization in each soil sample. The relative abundance of certain ECM morphotypes differed between burned and control plots, and the percentage of mycorrhizal tips was significantly lower in the burned than in the control plot. Nevertheless, there were no significant differences in the diversity, species richness or species composition of the ECM community in the burned and control plots. The dominant ECM morphotypes in both stands were Cenococcum geophilum and several thelephoroid fungi. Sphaerosporella brunnea and Pisolithus tinctorius thrived especially in the burned plot, whereas three ectomycorrhizal morphotypes assigned to the genus Hebeloma were especially abundant in the control plot. There was no significant variation in the relative abundance of the ECM morphotypes between seasons, but ECM community species richness was highest in autumn and lowest in summer. The percentage of mycorrhizal tips reached a maximum in winter, with its minimum in autumn. Collection of samples over the 3-year period also enabled us to detect a significant increase in percentage of ECM colonisation in the burned stand over time.
The following values have no corresponding Zotero field: accession-num: 15889285
Keywords: Annual variation; Ectomycorrhizae; Post-fire dynamics; Quercus ilex; seasonal variation

A revision of the descriptions of ectomycorrhizas published since 1961 - De Roman, Miriam; Clavería, Vanessa; Maria De Miguel, Ana (Mycological Research, 2005)
All available publications providing descriptions of ectomycorrhizas (ECM) were reviewed in order to build a database containing details on fungus forming the ECM, host tree, country where the material for description was collected, and habitat of the ECM. Other secondary data were also recorded. In all 1244 descriptions of ECM published since 1961 in 479 papers were reviewed. The number of diﬀerent ECM morphotypes described was 814. Most ECM described were collected in Europe and North America. Gymnosperms were the most common tree associates, and boreal and temperate forests the most studied ecosystems. Fungal symbionts were mostly Basidiomycota, epigeous, and with mushroom-like morphology. The paper also addresses the gaps in ECM knowledge that mycorrhizologists should address in future studies.
Keywords: descriptions; Ectomycorrhizae; habitat (PG); host tree